(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The purpose of the present study was to investigate the incidence of the supernumerary teeth among Palestinian according to sex, location and morphology. This retrospective study was carried out using 1683 panoramic radiographs (719 males, 964 females) aged seven and older. The supernumerary teeth were observed in 11 (0.65%) panoramic (4 males, 7 females) with (1:1.75) male female ratio. two cases of them showed bilaterally hyperdontia. The premolar was found to be the most common supernumerary, followed by mesiodens and distomolar. The incidence of supernumerary teeth was found to be 0.77%, and we demonstrate that parapremolar the most common in the mandible.